Two-Photon STED Microscopy for Nanoscale Imaging of Neural Morphology In Vivo - Ter Veer, Mirelle J T; Pfeiffer, Thomas; Nägerl, U Valentin (Methods in molecular biology (Clifton, N.J.), 2017)
The advent of super-resolution microscopy offers to bridge the gap between electron and light microscopy. It has opened up the possibility of visualizing cellular structures and dynamic signaling events on the "mesoscale" well below the classic diffraction barrier of light microscopy (10-200 nm), while essentially retaining the advantages of fluorescence microscopy concerning multicolor labeling, detection sensitivity, signal contrast, live-cell imaging, and temporal resolution.From among the new super-resolution techniques, STED microscopy stands out as a laser-scanning imaging modality, which enables nanoscale volume-metric imaging of cellular morphology. In combination with two-photon (2P) excitation, STED microscopy facilitates the visualization of the highly complex and dynamic morphology of neurons and glia cells deep inside living brain slices and in the intact brain in vivo.Here, we present an overview of the principles and implementation of 2P-STED microscopy in vivo, providing the neurobiological context and motivation for this technique, and illustrating its capacity by showing images of dendritic spines and microglial processes obtained from living brain tissue.